Pengembangan Media Video Gerak Tari Sparkling Surabaya pada Mata Pelajaran Seni Budaya bagi Siswa SMP - Rahajeng Lukitarini; Iskandar Wiryokusumo; Suhari (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2020)
Dance learning in general uses the method of imitating the movements given by the teacher. The teacher's limited ability to provide dance practice in class makes students are required to carry out dance practice independently. learn the motion of Sparkling dance in Surabaya. From the development of this video media produces Learning Videos of Sparkling dance in Surabaya as a tool for learning dance in the art of culture. The test subjects in the development of video media are material experts, media experts and design experts as well as junior high school students. Data collection techniques using questionnaire and test instruments.The results of the development of this video media based on expert review of the material is good, the design expert review is very good, and the media expert review is very good, the results of individual trials are good, the results of small group trials are good , and large group trials are good. With the media development of a variety of Sparkling Surabaya dance motion videos can improve student learning outcomes through pre-test results and test posts on junior high school students.